DAMPAK PENCEMARAN SUNGAI DI INDONESIA TERHADAP GANGGUAN KESEHATAN : LITERATURE REVIEW - Farida Sugiester S; Yura Witsqa Firmansyah; Wahyu Widiyantoro; Mirza Fathan Fuadi; Yana Afrina; Afdal Hardiyanto (Poltekkes Kemenkes Bandung, 2021)
River pollution in Indonesia is very high. throughout 2016, based on data from the Ministry of Environment and Forestry (LHK), out of 140 rivers in 34 provinces, 73.24% were in a polluted status. There are 2.01% of rivers that meet class 2 water quality standardsUsing this review literature approach to determine the relationship between river pollution and health problems based on the results of previous studies summarized in environmental health-based research.This research is a literature review. literature review is a methodology used in research that aims to collect and take the essence of previous research and analyze some of the expert's overview written in the text.The decrease due to water quality will reduce the usability, yield, productivity, and carrying capacity of water resources which in turn will worsen the natural resources depletion. Water sources are divided into 4 groups, namely surface water, ground water, rainwater and spring water. In several studies that have been analyzed, the water sources used are river water and well water.Based on the analysis that has been reviewed from the above research, it can be concluded that the community uses rivers and wells in their daily activities. This can be seen clearly from several studies that analyzed water quality from chemical, physical, and biological parameters that exceed quality standards. From this pollution, health problems such as skin disorders, dermatitis, and diarrhea are found.